CHRISTIANITY OF FUNDAMENTALISM AND SECULARISM: ARE THERE HINTS OF SOCIAL TEACHING WITHIN THE SERBIAN ORTHODOX CHURCH? (Религиски дијалог и соработка, 2025)
The scientific paper before us will question the role, scope and importance of OrthodoxChristianity in social issues, especially in the case of the Serbian Orthodox Church (SPC). The topicof the scientific work is focused on questioning the connections between the specifically Orthodoxexperience of religion and its place in contemporary (Serbian) society. Therefore, the viewsof church dignitaries of the Serbian Orthodox Church regarding the role of the Orthodox faithin social issues were selected as the subject of research. Through his research, the author has sethimself the goal of predicting the possibilities of establishing and building the social teaching ofthe Serbian Orthodox Church. The increasingly active role of religious communities and churchesin contemporary society: from culture, through politics and economy to the natural environmentpoints to the legitimate social significance of the basic assumptions of this scientific paper. Thequestioning of theoretical assumptions, religious conceptions and spiritual-political phenomena:fundamentalism, integralism and secularism on the example of an isolated case study in the ideasand value positions of dignitaries and theologians of the Serbian Orthodox Church leads to anindisputable innovative contribution and scientific justification of the research. After all, the SOChas always been the foundation of the national rallying of the Serbian ethnos, and the main leverof national identity, so the overall justification of the topic is greater. In the paper, the authorstarted from the initial assumption that the current opinion in the Serbian Orthodox Church isnot favorable towards the establishment of the social teaching of the Serbian Orthodox Church.The research was based on numerous methods in social sciences, such as: observation, case study,content analysis, comparative approach...